2019
DOI: 10.1017/s1479262118000485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the complete chloroplast genome sequences of three Amaranthus species

Abstract: The complete chloroplast (cp) genome sequences of three Amaranthus species (Amaranthus hypochondriacus, A. cruentus and A. caudatus) were determined by next-generation sequencing. The cp genome sequences of A. hypochondriacus, A. cruentus and A. caudatus were 150,523, 150,757 and 150,523 bp in length, respectively, each containing 84 genes with identical contents and orders. Expansion or contraction of the inverted repeat region was not observed among the three Amaranthus species. The coding regions were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…The ycf15 gene in the two reverse repeats was lost in S. przewalskii and S. bifolia , implying that their chloroplast genomes contained 131 genes. Our result was different from the previous result obtained for Gentianaceae ( Dong et al, 2020 ), which showed that the chloroplast genome of Gentianaceae had 67–80 protein-coding genes, 30 tRNA genes, and four rRNA genes. This difference mainly arose due to gene deletion between genera.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The ycf15 gene in the two reverse repeats was lost in S. przewalskii and S. bifolia , implying that their chloroplast genomes contained 131 genes. Our result was different from the previous result obtained for Gentianaceae ( Dong et al, 2020 ), which showed that the chloroplast genome of Gentianaceae had 67–80 protein-coding genes, 30 tRNA genes, and four rRNA genes. This difference mainly arose due to gene deletion between genera.…”
Section: Resultscontrasting
confidence: 99%
“…As can be seen from the comparison of chloroplast sections, such differences mainly occurred in the large single-copy (LSC) and IR regions. The chloroplast genome length of angiosperms is generally 115–165 kb and that of Gentianaceae is 137–154 kb, which is consistent with the length characteristics of angiosperms and Gentianaceae ( Li et al, 2018 ; Dong et al, 2020 ). Compared with other genera of Gentianaceae, the average chloroplast genome length of Swertia L. was similar to that of Halenia (153 kb), but shorter than that of Paedera (154 kb) ( Dong et al, 2020 ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The pseudogenization of the ycf1 gene may be interpreted as wastage in the course of species evolution, or as the fact that the species does not specifically need the gene. Moreover, the pseudogenization of ycf1 was also detected in the genera Paeonia and Aconitum [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one complete chloroplast genome sequences of Amaranthaceae including two Sueada chloroplast genomes (Kim et al 2016;Devi and Thongam 2017;Hong et al 2017;Park et al 2018;Hong et al 2019;Kim et al 2019aKim et al , 2019bMaughan et al 2019) were aligned by MAFFT 7.388 (Katoh and Standley 2013) after rearranging SSC and LSC regions of Chenopodium quinoa 'Real Blanca' for constructing neighbor joining (bootstrap repeat is 10,000) and maximum likelihood trees (bootstrap repeat is 1,000) using MEGA X (Kumar et al 2018). Phylogenetic trees show that two Suaeda chloroplast genomes were clustered with high bootstrap support ( Figure 1).…”
mentioning
confidence: 99%